La construction du sujet scolaire dans les recherches en Information-Documentation - Anne Cordier (Recherches en Éducation)
How to understand the « digital learning subject », i.e. the young student- information investigator in the research of information and Communication Science? The epistemological difficulties to address this issue are numerous: the generational approach stigmatizes this audience, while the user information approach is very normalizing. Information and Communication Science have yet much to part to understand this regard in all its complexity. We propose a link between information practices, attitudes and perceptions of operators, taking into account the social, material and symbolic spaces in which these practices register. To do this, it is necessary to affirm the formality of all information practices, the result of an encounter between individual and social logic through an ecological approach to information.